THE INFLUENCE OF HUMAN FACTORS ON THE UPBRINGING OF TWINS IN UZBEK FAMILIES (ResearchJet Journal of Analysis and Inventions, 2021)
The article presents the factors influencing the psychological development of twins, as well as the psychogenetic foundations of specific approaches to the upbringing of twins in Uzbek families.